2018
DOI: 10.22159/ijcpr.2018v10i2.25843
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Fruits and Vegetable Food as Nutritional Supplement for Diabetes, Obesity and Metabolic Diseases

Abstract: The most challenging diseases such as obesity and diabetes are growing wider and its treatment is a major challenge for healthcare professionals. Most of these metabolic diseases are because of the impact of lifestyle on health. Many studies have recognized a high intake of fruits, greens and other vegetables, nuts and pulses play an important role in our daily diet. Biological constituents are important to combat such diseases and can act as nutritional supplements for treatment of diabetes, cancer, obesity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…There is a need for effective add-on therapy like DPP-4 inhibitors besides existing standard therapy (metformin, glimepiride) to prevent uncontrolled diabetes and enhancing the efficacy of the treatment and reducing economic burden [22]. Although, International American Diabetes Association and local guideline recommended lifestyle management as the mainstay of treatment for T2DM; with metformin as the preferred initial oral antihyperglycemic agent in most of patients, there remains no consensus regarding which classes of agents to add as dual and triple therapy, if and when required [9][10][11]23]. Clinical trials have reported safety and efficacy of teneligliptin as DPP-4 inhibitors [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for effective add-on therapy like DPP-4 inhibitors besides existing standard therapy (metformin, glimepiride) to prevent uncontrolled diabetes and enhancing the efficacy of the treatment and reducing economic burden [22]. Although, International American Diabetes Association and local guideline recommended lifestyle management as the mainstay of treatment for T2DM; with metformin as the preferred initial oral antihyperglycemic agent in most of patients, there remains no consensus regarding which classes of agents to add as dual and triple therapy, if and when required [9][10][11]23]. Clinical trials have reported safety and efficacy of teneligliptin as DPP-4 inhibitors [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, junk food and dairy products are total prohibited instead skimmed milk can be a part of their diet. Pulses play an important role in weight control [12]. A diabetic diet promotes weight loss [13].…”
Section: Structured Exercise Program For Group Bmentioning
confidence: 99%
“…Metabolic syndrome (Met S) is an association of insulin resistance, high blood pressure, central obesity, arteriosclerosis, stroke, hyperlipoproteinemia, and heart infarction [1,2]. Met S is considered as lifestyle disorder because poor dieting and lack of regular physical activity lead to insulin resistance or insulin resistance-linked obesity, a condition where the body's cells are incapable of taking up glucose from the blood [3,4]. Visceral obesity, insulin resistance and chronic inflammation, is characterized by the production of abnormal adipocytokines such as tumor necrosis factor α, interleukin-1 and 6, leptin, and adiponectin [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%